Research of Ecological Behavior of Agglomerations Residents of Kazakhstan - A. M. Tleppayev; S. Zh. Zeinolla; S. Velesco (Экономика: стратегия и практика, 2022)
The purpose is to research the environmental and economic practices used by households in urban agglomerations. As is known, ecological behavior is a very important part of the value paradigms. Improvement of the environmental situation at the global level is possible only with the active participation of civil society, while country and regional specifics determine the research and development of effective approaches of a reasonable environment attitude. Kazakhstan with large territories has urgent problems in terms of air quality, water quality, waste management, biodiversity conservation, etc. The authors used a directional approach in the formation of a questionnaire, considering the peculiarities of residence at the place of residence and the characteristics of the respondents. This as result of the understanding that residents of urban agglomerations have wide access to information, infrastructure, communities and movements, which positively affects the dynamics of the formation of important skills, as well as more environmentally responsible behavior in behavior. Based on international experience, a research methodology included conducting a survey in three large Kazakhstan’s cities. The regression model used for quantitative results, which mathematically describe the degree of influence of individual variables on the overall indicator. As part of the research, three hypotheses determined how individual factors effect on environmental behavior, which made recommendations and conclusions. The results presented in the research used for a comparative analysis of the manifestation of the ecological behavior of the inhabitants of agglomerations. The results used for a comparative analysis of the ecological behavior of the inhabitants of agglomerations.